(untitled) (Journal of the Bangladesh Agricultural University, 2025)
Agriculture is one of the most potential export sectors of Bangladesh. With a view to unleashing the potential, a packing House named the Central Packing House was established by the Department of Agricultural Extension in 2017 at Shyampur, Dhaka. This study was conducted to assess the impact of the packing house on the export of fresh fruits and vegetables from Bangladesh to European countries. It was observed that the number of noncompliance cases from the importing European countries experienced a sharp downfall starting from 153 in 2015-16 to 61 in 2022-23. As a result, there was an overall magnificent development of the scenario. It was found that the center started with seventeen agricultural products destined to four countries only, which extended to 103 items and 13 countries in seven years only. The beginning rate of exportable items, the amount of export and earning of foreign remittances climbed up to 83%, 6836.32 metric tons and 25,08,000 USD from 50%, 1000 metric tons and 10,14,000 USD respectively from the commencing years. J Bangladesh Agril Univ 23(1): 18–24, 2025